Phase I, randomized, observer-blind, placebo-controlled studies to evaluate the safety, reactogenicity and immunogenicity of an investigational non-typeable Haemophilus influenzae (NTHi) protein vaccine in adults. Issue 27 (8th June 2016) - Leroux-Roels, Geert; Van Damme, Pierre; Haazen, Wouter; Shakib, Sepehr; Caubet, Magalie; Aris, Emmanuel; Devaster, Jeanne-Marie; Peeters, Mathieu
Abstract: Background: Non-typeable Haemophilus influenzae (NTHi) is a major cause of various respiratory diseases. The development of an effective vaccine against NTHi mandates new approaches beyond conjugated vaccines as this opportunistic bacterium is non-encapsulated. Here we report on the safety, reactogenicity and immunogenicity of a multi-component investigational vaccine based on three conserved surface proteins from NTHi (proteins D [PD], E [PE] and Pilin A [PilA]) in two observer-blind phase I studies. Methods: In the first study (NCT01657526 ), 48 healthy 18–40 year-olds received two vaccine formulations (10 or 30 μg of each antigen [PD and a fusion protein PE-PilA]) or saline placebo at months 0 and 2. In the second study (NCT01678677 ), 270 50–70 year-olds, current or former smokers, received eight vaccine formulations (10 or 30 μg antigen/dose non-adjuvanted or adjuvanted with alum, AS01E or AS04C ) or saline placebo at months 0, 2 and 6 (plain and alum-adjuvanted groups) and at months 0 and 2 (AS-adjuvanted groups). Solicited and unsolicited adverse events (AEs) were recorded for 7 and 30 days post-vaccination, respectively; potential immune-mediated diseases (pIMDs) and serious AEs (SAEs) throughout the studies. Humoral and antigen-specific T-cell immunity (in study 2 only) responses were assessed up to 12 months post-vaccination. Results: Observed reactogenicity was highest in the AS-adjuvanted groups but no safety concerns were identified with any of the NTHi vaccine formulations. One fatal SAE (cardiac arrest) not considered related to vaccination, and one pIMD (non-serious psoriasis) in the Placebo group, were reported post-dose 3 in Study 2. All formulations generated a robust antibody response while the AS01-adjuvanted formulations produced the highest humoral and cellular immune responses. Conclusion: This study confirms that the NTHi vaccine formulations had an acceptable reactogenicity and safety profile and were immunogenic in adults. These results justify further clinical development of this NTHi vaccine candidate.